2013
DOI: 10.1007/s11999-013-3181-6
|View full text |Cite
|
Sign up to set email alerts
|

The John Charnley Award: Diagnostic Accuracy of MRI Versus Ultrasound for Detecting Pseudotumors in Asymptomatic Metal-on-Metal THA

Abstract: Background The prevalence of pseudotumors in patients with large-head metal-on-metal (MOM) THA has been the subject of implant recalls and warnings from various regulatory agencies. To date, there is no consensus on whether ultrasound or MRI is superior for the detection of pseudotumors. Questions/purposes We prospectively compared ultrasound to MRI for pseudotumor detection in an asymptomatic cohort of patients with MOM THAs. We also compared ultrasound to MRI for assessment of pseudotumor growth and progress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
73
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(74 citation statements)
references
References 25 publications
1
73
0
Order By: Relevance
“…Patients with a well-functioning MoM hip implant (nine resurfacings and three THAs) at 5 or more years postimplantation who did not have a pseudotumor, as demonstrated sonographically [8], served as the control group. All ultrasounds were performed by a fellowshiptrained musculoskeletal radiologist (RF).…”
Section: Patient Groupsmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients with a well-functioning MoM hip implant (nine resurfacings and three THAs) at 5 or more years postimplantation who did not have a pseudotumor, as demonstrated sonographically [8], served as the control group. All ultrasounds were performed by a fellowshiptrained musculoskeletal radiologist (RF).…”
Section: Patient Groupsmentioning
confidence: 99%
“…Patients with a well-functioning implant were assessed at the latest postoperative clinical followup (6 ± 1 years [mean ± SD]; range, 5-8 years) with the WOMAC and the UCLA activity scores. WOMAC scores were 100 (94-100) (median with interquartile range), 88 (75-88), 98 (95-100), and 94 (92-97) for pain, stiffness, function, and total score, respectively, and the UCLA score was 8 (6)(7)(8). Patients with a WOMAC score lower than 75 for stiffness and lower than 80 for pain, function, and total score, and/or a UCLA score lower than 6 (with 10 being the best score) were excluded from the study.…”
Section: Patient Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation implies that earlier recognition of the clinical entity and diagnosis prompting earlier intervention may play a role in reducing the complications associated with wear and corrosion. Current research is focusing on routine use of three-dimensional imaging to diagnose corrosion and MoM wear problems before there is extensive soft tissue damage [16,35]. Many of the studies we identified also mentioned the use of metal level testing.…”
Section: Discussionmentioning
confidence: 99%
“…Proposed advantages of MoM bearings in THA include decreased wear, lower frequencies of dislocation, greater ROM, and an improved ability to withstand high-impact activities [14]. However, concerns have arisen with the use of large MoM bearings as a result of reports of catastrophic aseptic reactions resulting in soft tissue destruction, periprosthetic osteolysis, and associated complications [2,13,15,21,22].…”
Section: Introductionmentioning
confidence: 99%